Litterärt värde ur första- och tredjepersonsperspektiv - Löfgren, Ingeborg (Tidskrift för litteraturvetenskap, 2025)
Literary Value Viewed from a First-Person Perspective versus a Third-Person Perspective This article investigates the logical differences between approaching, and trying to understand, literary value from a first-person and a third-person perspective, respectively. The article takes as its point of departure an essay by Fredrik Hertzberg, ”Farväl kvalitet. Farväl konst.” Om litterärt värde (2023), that stirred a heated debate about literary criticism in Finland in the autumn of 2023 and spring of 2024. In his essay, Hertzberg critiques Barbara Herrnstein Smith’s seminal work, Contingencies of Value (1988), as well as scholarship and criticism that investigate literary value inspired by her theorizing. Hertzberg claims that Herrnstein Smith’s understanding of literary value is highly distortive. In this article, I argue that both Hertzberg and Herrnstein Smith (and those working within the tradition of her thought) make valid knowledge claims about literary value. But while Hertzberg approaches literary value from a first-person perspective, Herrnstein Smith (and scholars who follow her lead) is (mainly) interested in literary value as it appears from a third-person perspective. Both perspectives can yield important insights, but trouble ensues when we get these different perspectives mixed up. By appealing to Ludwig Wittgenstein’s notion of aspect-seeing, and Stanley Cavell’s discussion of aesthetic “fraudulence”, the article sets out to demonstrate how the first- and third-person perspectives elicit different aspects of literary value. It argues that as long as we are aware of the important logical differences pertaining to the two perspectives, we are enriched by thinking about literary value through both of them.